Age-specific cerebral haemodynamic effects of early blood pressure lowering after transient ischaemic attack and non-disabling stroke. (September 2021) - Mazzucco, Sara; Li, Linxin; McGurgan, Iain J; Tuna, Maria A; Brunelli, Nicoletta; Binney, Lucy E; Rothwell, Peter M; ,
Introduction: There is limited knowledge of the effects of blood pressure (BP) lowering on cerebral haemodynamics after transient ischaemic attack (TIA) and non-disabling stroke, particularly at older ages. We aimed to evaluate changes in transcranial Doppler (TCD) haemodynamic indices in patients undergoing early blood pressure lowering after TIA/non-disabling stroke, irrespective of age. Patients and methods: Among consecutive eligible patients attending a rapid-access clinic with suspected TIA/non-disabling stroke and no evidence of extra/intracranial stenosis, hypertensive ones underwent intensive BP-lowering guided by daily home telemetric blood pressure monitoring (HBPM). Clinic-based BP, HBPM, End-tidal CO2 and bilateral middle cerebral artery (MCA) velocity on TCD were compared in the acute setting versus one-month follow-up; changes were stratified by baseline hypertension (clinic-BP≥140/90) and by age (<65, 65–79 and ≥80). Results: In 697 patients with repeated TCD measures, mean/SD baseline systolic-BP (145.0/21.3 mmHg) was reduced by an average of 11.3/19.9 mmHg ( p < 0.0001) at one-month (133.7/17.4 mmHg), driven by patients hypertensive at baseline (systolic-BP change = −19.0/19.2 mmHg, p < 0.001; vs −0.5/15.4, p = 0.62 in normotensives). Compared with baseline, a significant change was observed at one-month only in mean/SD MCA end diastolic velocity (EDV) (0.77/7.26 cm/s, p = 0.005) and in resistance index (RI) (−0.005/0.051, p = 0.016), driven by hypertensive patients (mean/SD EDV change: 1.145/6.96 cm/s p = 0.001, RI change −0.007/0.06, p = 0.014). Findings were similar at all ages (EDV change – ptrend =0.357; RI change – ptrend =0.225), including 117 patients aged ≥80. EDV and RI changes were largest in 100 patients with clinic systolic-BP decrease ≥30 mmHg (mean/SD EDV change = 2.49/7.47 cm/s, p = 0.001; RI change −0.024/0.063, p < 0.0001). Conclusion: There was no evidence of worsening of TCD haemodynamic indices associated with BP-lowering soon after TIA/non-disabling stroke, irrespective of age and degree of BP reduction. In fact, EDV increase and RI decrease observed after treatment of hypertensive patients suggest a decrease in distal vascular resistance.